Power system control under cascading failures : understanding, mitigation, and system restoration /: understanding, mitigation, and system restoration. (2018) - Sun, Kai, 1976-; Hou, Yunhe, 1975-; Sun, Wei, 1982-; Qi, Junjian, 1985-
No abstract available